Financial spillover effects in supply chains: Do customers and suppliers really benefit? - Erik Hofmann; Yannick Sertori (Logistics, 2020)
Studies have shown that leading supply chain companies are associated with significantly higher company financial ratios than competitors. In contrast, little research has focused on the financial performance of the affiliated suppliers and customers of such supply chain leader (SCL) companies. Thus, the central purpose of this paper is to determine, from a financial perspective, whether suppliers and customers benefit or lose by participating in a SCL network (so called "financial spillover effects"). Companies that were ranked in the Gartner Supply Chain Top 25 were selected as SCLs. For each selected firm, the five largest suppliers and customers were identified and compared with a control sample from the same industry. In order to elaborate on existing insights into the (financial) outcome of supply chain relationships, we applied an explorative approach with abductive reasoning, while comparing the secondary data for 224 SCL supplier (56 firms) and 168 SCL customer (42 firms) firm-years with 1940 (485 firms) and 1544 (386 firms) control firm-years, respectively. The following insights are made: First, the superior financial performance of SCLs was confirmed. Second, the financial performance of suppliers and customers showed superior liquidity and activity ratios but inferior profitability ratios. Third, suppliers showed much more significant results than customers.
Keywords: 650; financial performance; liquidity redistribution; profitability waiver; supply chain excellence; supply chain finance; supply chain relationship; Wilcoxon signed rank test